A multidisciplinary approach to caring for a pregnant patient with blue rubber bleb nevus syndrome: A case report - Sydney Daviskiba; Hannah Shuman; Mariam Ayyash; Gayathri Vadlamudi; Stefan Smietana; Gregory Goyert (Elsevier, 2022)
Blue rubber bleb nevus syndrome (BRBNS) is a rare vascular disorder characterized by recurrent, multifocal venous malformations throughout the skin, soft tissue, and numerous internal organs. Pregnant women with BRBNS are at high risk of morbidity and mortality, and thus their care requires careful planning and surveillance. This report highlights the case of a 21-year-old woman, gravida 1, para 0, with BRBNS who was cared for by a multidisciplinary team of providers in obstetrics, maternal-fetal medicine, obstetric anesthesia, hematology, dermatology, gastroenterology, and otorhinolaryngology. The report provides a comprehensive guide to the multidisciplinary management of pregnancy and delivery for patients with BRBNS.